(untitled) (Journal of Bangladesh Academy of Sciences, 2015)
Polyvinylchloride sheets (PVCS) as well as sandwiched composites of untreated jute-mat (JM)/PVC (UJPC) and organic acid treated JM/PVC (TJPC) were prepared with various JM contents by compression molding method at 160ºC. Mechanical, chemical textural, surface morphological, thermal and water intake (WI) properties of these samples were measured using a universal testing machine, a Fourier transform infrared (FTIR) spectrometer, a scanning electron microscope, a thermal analyzer and the gravimetric method, respectively. Young modulus (Y) and tangent modulus (G) of TJPC are found to increase from UJPC. FTIR spectra clearly exhibited distinct absorption peaks of UJPC and TJPC, indicating a modified texture of treated JM. The observed WI value was lower in TJPC than UJPC. Fiber-tearing of fractured surface micrographs observed for TJPC and fiber pull-out for UJPC suggested a good adhesion between JM and PVC in the former one. Most importantly, the activation energy (Ea) analysis by Ozawa method gives its value of 164 KJ/mol for TJPC and 135 KJ/mol for UJPC. Journal of Bangladesh Academy of Sciences, Vol. 39, No. 1, 13-23, 2015